Exergy, Energy, Economic, and Environmental Assessment of Gas Condensate Stabilization Units for the Selection of Optimum Configuration - Van Vang Le; Elizabeth C. Matsui (Advances in Engineering and Intelligence Systems)
In this paper, five structures for gas condensate stabilization are simulated and analyzed from the energy, exergy, economic and environmental points of view. These structures are simulated using Aspen HYSYS and Peng-Robinson fluid package. The studied structures are stabilizer column with reboiler and condenser and without preheating (STB-A), stabilizer column with reboiler and without condenser (STB-B), stabilizer column with reboiler, without condenser and with preheating (STB-C), stabilizer column with reboiler, condenser and preheater (STB-D), and stabilizer column with reboiler, without condenser and with side reboiler (STB-E). Exergy efficiency, total production cost, reboiler energy, and total CO2 emission are calculated for all the structures and compared. According to the performed analysis, STB-E with exergy destruction of 681.9 kW has the highest exergy efficiency (36.37%) among all the studied structures. In addition, technical assessment showed that the STB-C has the highest loss of hydrocarbons through the overhead vapors of the stabilization column. Based on the economic analysis it is deduced that the values of total production costs in STB-C, STB-D, and STB-E are 7.14% lower than the total production costs values of the structures without integration (STB-A and STB-B). Finally, it is determined that the STB-E is the only structure that can maintain the quality of RVP (8 psia) for the produced condensate while simultaneously controlling all the technical, economic and, environmental parameters at desirable levels.